One Function to Rule Them All: An R Shiny Application and R Script for Processing Measurement Data in Microscopic Analysis of Linear Enamel Hypoplasia. - Sellers, Maria L.; Temple, Daniel H. (American Journal of Biological Anthropology, 2026)
The quantities of data required for microscopic analyses of linear enamel hypoplasia (LEH) require familiarity with software coding to provide objective definitions of enamel defects. Here we provide a pre‐built R script and R Shiny application for identifying accentuated perikymata from microscopic measurements and calculating the age‐at‐defect by individual and tooth. Our R Shiny application is designed to facilitate analysis based on a method introduced by Bocaege and Hillson (2016) which uses LOWESS residuals objectively define abnormally large perikymata indicative of LEH defects. Example data from the right mandibular first and second incisors from an individual dating to the Middle/Late Colonial period (ca. A.D. 1620–1750) buried at the Chapel of Santa Maria de Magdalena de Eten (CSMME) has been included to demonstrate how the code facilitates LEH analysis. This code represents a move towards further standardization of identifying enamel defects, as well as a means of reducing the time and energy required for analysis on the part of the researcher. This program aims to reduce the risk of error by use of a common code, encourage continued use of these methods for identifying and analyzing LEH, and provide open access to these codes so that future research may build or improve upon these methods.